Impact of Pharmacist-Led Interventions On Medication Adherence in Patients with Chronic Psychiatric Disorders: Pharmacist On Medication Adherence in Patients with Chronic Psychiatric Disorders - Haq, Usman Ul; Ellahi, Shaheer; Khan, Zirak; Mansoor, Aneeqa (Pakistan Journal of Health Sciences, 2025)
Mental health disorders represent a growing global health challenge, affecting an estimated 970 million people worldwide as of 2019. These disorders not only impair individuals' ability to function but also impose significant economic and social burdens. In a country like Pakistan, mental health treatment resources are minimal, and chronic psychiatric disorders like bipolar personality disorder, schizophrenia, and chronic depression have become an enormous burden. Objectives: To assess the impact of pharmacist-led interventions on medication adherence among psychiatric patients in Rawalpindi, Pakistan. Methods: This quasi-experimental mixed-method study employed a pre-post intervention design. Conducted in two psychiatric clinics in Rawalpindi, it involved a total sample of 60 participants for the quantitative phase and 10 for the qualitative phase. Quantitative data were analyzed using McNamara’s test and the Wilcoxon signed-rank test, while qualitative data underwent thematic analysis. Results: Significant improvements in medication adherence were observed post-intervention, as evidenced by Paired Chi-Square (McNamara’s test) and Wilcoxon Signed Rank Test. Thematic analysis of the qualitative data identified four main themes with three sub-themes, providing insights into the patients’ attitudes, knowledge, and practices regarding medication adherence. Conclusions: It was concluded that pharmacist-led interventions were found to be effective in enhancing medication adherence among psychiatric patients. The study underscores the importance of ongoing support and education for this patient group and recommends the continuation of such interventions to sustain improvements in adherence.